Oxaliplatin-Induced Peripheral Neuropathy Grade in Females with Colorectal Cancer Patients - Inas Moawya Ahmed; Lamia Elwakeel; Amr S. Tawfik; Raafat Ragaie Abdel-Malek (Ain Shams University, 2019)
The oxaliplatin-based regimen is considered an important standard of care for patients with colon cancer (CC). Neurotoxicity is the most relevant non-hematologic toxicity of oxaliplatin. The current study aimed to assess the association between colorectal cancer patient's (CRC) gender and susceptibility of oxaliplatin-induced sensory and motor peripheral neuropathy grades in Egyptian patients. All eligible patients between 18-75 years old with CRC were included in the study and only those who had a neurologic disease or diseases impairing neurologic function were excluded. Then eligible patients were stratified into two groups according to gender; oxaliplatin-induced peripheral neuropathy (OIPN) was evaluated and graded on day 1 of each chemotherapy cycle for 12 cycles according to the National Cancer Institute Common Terminology Criteria for Adverse Events (NCI-CTCAE), version 4.0 from March 2015 to October 2017. From a total of 47 females and 33 males; 41(87.2%) females and 29 (87.9%) males suffered from different grades of sensory and motor peripheral neuropathy.Regarding sensory oxaliplatin-induced peripheral neuropathy (OIPN), females had a higher risk of grade II-III PN than males (92.7% versus 58.6% respectively; p =0.001) For motor OIPN, females were more susceptible to grade II-III PN versus males (84.6% versus 56.5% respectively; p=0.015). In conclusion, High grade (grade II-III) Oxaliplatin-induced sensory and motor peripheral neuropathy occurred more frequently in females versus males Egyptian colorectal cancer patients.